The attitudes of Icelandic journalists towards controversial news-gathering practices - Guðmundsson, Friðrik Þór; Jóhannsdóttir, Valgerður (Félagsfræðingafélag Íslands, 2023)
In this article we focus on the attitudes of Icelandic journalists towards various professional ethic codes and news-gathering practices that can otherwise be considered “unconventional”, and are often controversial, such as the use of hidden cameras, the use of confidential documents without authorization or concealing their journalist’s identity. We use data from a survey that was submitted to news journalists in Iceland in the spring of 2021. The survey is part of the international comparative study, Worlds of Journalism Studies. A similar survey was conducted in 2012, and the findings of these two surveys are compared to analyze changes in the attitudes of Icelandic journalists over the past decade. The results show that the use of hidden recording devices and the use of confidential business or government documents enjoys strong and widespread support within the profession. Support for concealing one´s journalist’s identity has grown significantly, but the use of private data is more controversial. Í þessari grein er fjallað um viðhorf blaða- og fréttamanna á Íslandi til siðareglna fagsins og ýmissa vinnubragða við öflun upplýsinga sem að öðru jöfnu geta talist óhefðbundin og eru gjarnan umdeild, svo sem notkun falinna myndavéla, notkun trúnaðargagna í heimildarleysi og þess að villa á sér heimildir. Byggt er á gögnum úr spurningakönnun sem lögð var fyrir blaða- og fréttamenn hér á landi vorið 2021. Könnunin er hluti alþjóðlegrar samanburðarrannsóknar, Worlds of Journalism Study. Sambærileg könnun var gerð árið 2012 og eru niðurstöður kannananna tveggja bornar saman til að greina breytingar á viðhorfum íslenskra blaða- og fréttamanna. Niðurstöðurnar sýna að notkun falinna upptökutækja og notkun trúnaðarskjala úr stjórnsýslu eða viðskiptalífi nýtur mikils og víðtæks stuðnings innan fagsins. Stuðningur við að villa á sér heimildir við upplýsingaöflun hefur aukist umtalsvert, en notkun einkagagna er umdeildari.